Mayor: Relief rules must change - Wildermuth, Todd (Raton, NM Raton Range, 1996)
This article is about relief after the tornado.
Newspaper article and Photographs of the Old West Trading Post and the International Bank building.
Mater List Item # 3
File location is in the New Mexico File Cabinets
Keywords: Rogers, Harl -- Mayor; Nagurka, Stu; Richardson, Bill -- U.S. Senate Representative; Domenici, Pete -- U.S. Senate Representative; City of Cimarron; Federal Emergency Management Agency (FEMA); Small Business Administration (SBA); Kit Carson Lounge; Tornado Cleanup; Tornado Relief; Relief Laws; Relief Practices; Fund Raisers; Cimarron, New Mexico